Factors associated with oral health-related quality of life in homeless persons: a cross-sectional study - Raissa Marielly Parente BERNARDINO; Aryvelto Miranda SILVA; Jonathan Ferreira COSTA; Marcus Vinícius Barbosa SILVA; Isaac Torres dos SANTOS; Neusa Barros DANTAS NETA; Raimundo Rosendo PRADO JÚNIOR; Regina Ferraz MENDES (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract This study aimed to evaluate the clinical and sociodemographic factors associated with the oral health-related quality of life (OHRQoL) of homeless persons. A cross-sectional study was conducted, with participants (n = 176) attending a Specialized Reference Center for the Homeless Population in Teresina, Brazil. Dental caries (DMFT index, WHO criteria), periodontal disease (CPI index), and the consequences of untreated caries (PUFA index) were measured by a single calibrated examiner (Kappa ≥0.83). Sociodemographic, oral health, and OHRQoL (OHIP-14) data were obtained through interviews. Data analysis included descriptive statistics and Poisson regression, with a significance level of 5%. Most of the participants were male (86.4%) and from the age group of 30 to 43 years (52.2%). Mean DMFT was 11 (SD ± 6.9) and mean total PUFA score was 1.2 (SD ± 2.2). Most of the participants (88.6%) had dental calculus and 8.5% and 1.7% of the sample had gingival bleeding and periodontal pocket > 3.5mm, respectively. The highest prevalence of negative impact in the OHRQoL was associated with females (1.4 (95%CI 1.1-1.7)), low educational level (2.0 (95%CI 1.3-3.0)), caries (1.6 (95%CI 1.1-2.6)), fistulas (1.9 (95%CI 1.3-3.1)), gingival bleeding (1.7 (95%CI 1.1- 2.7)), dental calculus (1.8 (95% CI 1.3-2.5)), periodontal pockets > 3 mm (1.5 (95%CI 1.1-2.0)), and need for extraction (2.3 (95%CI 1.1-5.0)). In conclusion, the negative impact on the OHRQoL of homeless persons was associated with low educational level, presence of decayed teeth, gingival bleeding, and dental calculus.